EDUCATIONAL PROCESS AND INNOVATIVE MANAGEMENT IN MODERN PEDAGOGY IN HIGHER SCHOOL - Sarsenbayeva, K.A.; Utegenova, Zh.S. (Academic Journal of Physical and Chemical Sciences, 2018)
According to the authors, in the world tendencies towards a change in the content of education, methods and forms of work with students, associated with the newly emerging concepts of higher education, are increasing. The education system of students is experiencing an innovation process, and the quality of management in modern pedagogy is the main priority of a vocational school, that is, the preparation of the personality of a specialist, professionally competent, competent, creatively developing, dominated by spiritual and moral humane qualities. In this regard, there is an increasing need to enhance the creativity of teachers in the process of using modern pedagogical technologies that will ensure the satisfaction of the demands of modern pedagogical practice. Currently, for a future teacher, mediocre possession of some baggage of knowledge and skills is not enough; his constant readiness for change, readiness for creativity is necessary.